Prevalência da infecção pelo vírus da hepatite c em indivíduos portadores de doenças oncohematológicas em Goiânia-GO - Marinho, Tássia Augusto (2013)
According to the World Health Organization (WHO), approximately 150 million people are chronically infected with hepatitis C virus (HCV) and 350 million people die each year from liver complications related to infection. HCV, as well as hepatotropic can infect and replicate in peripheral blood lymphocytes and mononuclear cells can induce a weak disorder oncohematológica. As the etiology of most diseases oncohematológicas is still unknown, some authors have suggested the role of this virus in the genesis of lymphomas. This study aimed to investigate the profile seroepidemiological study of hepatitis C infection in patients with disorder oncohematologicas attended at two hospitals in reference to the treatment of these diseases (Hospital Araújo Jorge e Hospital das Clínicas) in Goiânia, Goiás. A total de 350 individuals were recruited in hospitals, from june/2011 to february/2012 (Hospital Araújo Jorge) and June/August/2012 (Hospital das Clínicas) were interviewed and underwent blood collection. All samples were tested for the presence of antibodies to HCV (anti-HCV) using an enzyme-linked immunosorbent assay (ELISA) and immunoblot. The anti-HCV positive samples were submitted to HCV RNA detection by polymerase chain reaction (PCR) and genotyped by reverse hybridization by the Line Probe Assay (LiPA) method. The HCV infection prevalence was 0.86% (95% CI: 0.22 to 2.7) in patients with diseases oncohematológicas. The viral RNA was detected in 0.57% (2/3) of anti-HCV positive samples, and the genotype/subtype 1b, were identified in the study population. Risk characteristics, reported by individuals anti-HCV positive, use non-injecting drug use, blood transfusion before 1994, tattooing, surgery and multiple sexual partners. This research showed low prevalence of hepatitis C in the population studied. However, epidemiological investigations are relevant for analyze the effectiveness of intervention measures for control and prevention of this infection.